An Improved Method for Age Group Classification using Facial Features - Tomar, A; Kumare, JS (International Journal of Computer Sciences and Engineering, 2025)
Most of the facial features recognition, say for an example, character, gender and expression has been broadly envisioned. Programmed age assessment and prediction of future expressions have once in a while been examined. With the increase in age of human beings, we can see some gradual changes in their facial features. This paper aims to give a procedure to gauge age gathering that makes use of facial features. This procedure takes account of three stages namely Location, Feature Extraction and Classification. The geometric components of face pictures such as face edge, wrinkle topography, left eye to right eye separation, eye to nose separation, eye to jaw separation and eye to lip separation are calculated. By considering the surface and shape data, age grouping is done making use of K-Means bunching calculation. Age features are further ordered progressively based on the gathered data making use of K-Means bunching calculation. The acquired results are pretty fast and efficient. This paper can further be utilized for anticipating future confronts, arranging gender orientation, and expression recognition from images of the various faces.